PENERAPAN MODEL LEARNING STARTS WITH A QUESTION (LSQ) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 2 DEMAK TAHUN PELAJARAN 2013/2014 - Selamet Winarni; Ngurah Ayu Nyoman Murniati; Duwi Nuvitalia (Universitas PGRI Semarang, 2014)
Classroom action research this used Learning Starts with a Question model . This research is motivated by the learning outcomes of students of class XI IPA-4 SMAN 2 Demak in learning physics is lower than other classes. This study aims to improve student learning outcomes class XI IPA SMA N 2 Demak of academic year 2013/2014. The subjects were students of class XI IPA-4 SMA N 2 Demak totaling 40 students, consist of 12 male students and 28 female students.Classroom action research through three cycles of learning. Where each cycle consists of planning, action, observation, and reflection. Data collected through testing, observation method and documentation method.The results showed this learning by applying Learning Starts with a Question (LSQ) model to improve learning outcome student at each cycle. The conclusion of this research is the application of Learning Start with a Question (LSQ) model to improve learning outcomes student class XI IPA SMA N 2 Demak academic year 2013/2014.